School climate and its effects towards job satisfaction of secondary school teachers in Kuching Division / Khaliza Senak - Senak, Khaliza (2013)
This purpose of this study is to identify the type of school climate and the effects of school climate on teacher's job satisfaction among secondary school teachers in Kuching Division. A total of 417 teachers from 6 secondary schools in Kuching Division were involved as respondents in this study. Data was collected using questionnaires and cluster sampling technique was used to select a sample. Descriptive Statistics, Factor Analysis, Independent Sample T-test, One-Way ANOVA and Pearson correlation coefficient were used to analyses the data. The findings from this study indicated that the types of school climate as perceived by the secondary school teachers are disengaged climate and open climate. The findings also concluded that there was no significant difference of perception between gender and designation with four different types of school climate, while there were significant differences of perception for age groups and teaching experience with Engaged Climate. However, there were significant differences of perception between the race with Open Climate and Disengaged Climate, and also there was a significant difference of perception between teacher's qualifications with Open Climate. The results of the study also indicated that there was a significant but weak relationship between job satisfaction with Closed Climate and Disengaged Climate. The research findings will be of valuable use to the school administrators and the Ministry of Education about the important aspects needed in the working environment among secondary school's teacher in order to promote high job satisfaction and positive school climate. Secondary school teachers will also know the type of climate that exists in schools, the importance of school climate and its effects to their working environment.